The Relationship Between Renal Stones and Primary Aldosteronism - Chang, Chun-Kai; Chang, Chin-Chen; Wu, Vin-Cent; Geng, Jiun-Hung; Lee, Hsiang-Ying (Frontiers in Endocrinology, 2022)
Introduction The association between primary aldosteronism (PA) and nephrolithiasis is still unclear. The hypercalciuria and hypocitraturia of PA patients might be the reason leading to recurrent calcium nephrolithiasis. This study aimed to evaluate the relationship between PA and renal stones, including stone size and density. Materials and Methods From February 2010 to March 2021, we retrospectively collected 610 patients who presented to our medical center with hypertension history, and all these patients, suspicious of PA, had PA data survey. In total, 147 patients had kidney stone and were divided into 44 patients with essential hypertension as group 1 and 103 patients with PA as group 2. Pearson χ2 test and independent Student’s t-test were performed to examine the differences among variables. Results The mean age was 54.4 ± 12.0 years in group 1 and 53.0 ± 11.1 years in group 2. The incidence rate of renal stones in the PA group was around 24%. No significant differences between the two groups were found for gender, systolic/diastolic blood pressure, duration of hypertension, diabetes mellitus history, and laterality of kidney stone; however, mean stone size was 4.0 ± 3.3 mm in group 1 and 6.5 ± 7.2 mm in group 2, with a significantly larger renal stone size noted in the PA group than that in the essential hypertension group (p = 0.004). Hounsfield unit (HU) density was higher in the PA group vis-à-vis the essential hypertension cohort, although this did not reach a significant difference (p = 0.204). Conclusions Our study revealed that PA patients had a higher incidence rate of renal stones compared to that of the general population. Besides, the PA-related renal stones also presented as larger and harder than those of the essential hypertension group. Further investigation concerning the association between PA and renal stones is warranted.